Risk of Pneumonitis with the Use of Different Immune Checkpoint Inhibitors in a Mexican Population - Dávila-Dupont, David; Motola-Kuba, Daniel; Dorantes-Heredia, Rita; González-Alonso, Blanca K.; Alcántara-Velarde, Thalía; García-Santisteban, Rodrigo; Martínez-Sámano, Julio Eduardo; Grimaldo-Roque, Hiram Josué; Ruiz-Morales, José Manuel (My University, 2019)
Purpose: The incidence of pneumonitis reported in previous trials in patients with advanced cancer and use of programmed cell death protein 1 (PD-1) immunotherapy inhibitors was 2.7-3.6%. However, none of these trials included Mexican populations. Methods: This was a retrospective analysis involving 87 patients with advanced cancer who received PD-1 inhibitors as part of their therapy. The primary outcome was the incidence of pneumonitis after using PD-1 inhibitors. The secondary outcomes were major risk factors and radiological patterns of pneumonitis. Results: We found 13 cases of pneumonitis, giving an overall incidence of 15%; three of the cases were high-grade (grade 3). A ground-glass pattern was the major form found by chest computed tomography scans. We did not find any significant risk factor for pneumonitis. Conclusion: The incidence of pneumonitis secondary to treatment with PD-1 inhibitors in our Mexican population was 15%, which is 5 times higher than that found in other studies. No risk factor was identified for this increased incidence of drug-induced pneumonitis following the use of PD-1 inhibitors. © 2019 S. Karger AG, Basel. All rights reserved.